Nitrophenyl-EGTA, a photolabile chelator that selectively binds Ca2+ with high affinity and releases it rapidly upon photolysis. - Ellis-Davies, G C (1994)
The synthesis and properties of a caged calcium are described. The compound is an ortho-nitrophenyl derivative of EGTA. It is synthesized in 10 steps and with 24% overall yield. The photosensitive chelator, nitrophenyl-EGTA, has a Kd value for Ca2+ of 80 nM and for Mg2+ of 9 mM. Upon exposure to UV radiation (approximately 350 nm), the chelator is cleaved, yielding iminodiacetic acid photoproducts with low Ca affinity (Kd = 1 mM). The quantum yield of photolysis of nitrophenyl-EGTA in the presence of Ca2+ is 0.23 and in the absence of Ca2+ is 0.20. In experiments with chemically skinned skeletal muscle fibers, a fully relaxed fiber equilibrated with nitrophenyl-EGTA-Ca2+ complex, in the presence of 1 mM free Mg2+, maximally contracted after a single flash from a frequency-doubled ruby laser (347 nm). Half-maximal tension was achieved in 18 ms at 15 degrees C. Nitrophenyl-EGTA provides a tool for the investigation of the mechanism of Ca(2+)-dependent physiological processes, since under conditions of normal intracellular Ca2+ and Mg2+ concentrations, only Ca2+ is bound by the photolabile chelator and on illumination released rapidly and in high photochemical yield.